Outbreak of Intoxication by Senna occidentalis in Cattle - Horn, Joel Felipe; Schimitt, Ricardo; da Silva Fonseca, Ruth Ely; Keil, Eduarda; Zillig Echenique, Joanna Vargas; Emanoelly Machado Sousa da Silva, Emanoelly; Ricardo Nascimento Rocha, Ricardo; Coelho, Ana Carolina Barreto (Acta Scientiae Veterinariae, 2024)
Background: Senna occidentalis, often known as fedegoso, is an annual shrub of the Leguminosea family with myotoxic properties. All parts of the plant are toxic, but the seeds have the highest concentration. Ingestion occurs through the consumption of contaminated feed and, on rare occasions, through spontaneous ingestion in the middle of the pasture. Spontaneous intoxication has been described in cattle, swine, and horses. It typically manifests in cattle above one year of age, in the form of high lethality outbreaks. This study describes an outbreak of spontaneous intoxication by S. occidentalis in extensively raised cattle in the municipality of Gravataí, RS, Brazil. Cases: The farm provided a lot of 43 yearling calves, aged 12-18 months, assigned to the rearing system in May, with Tifton pasture and native field. The animals had access to an old vegetable field, which had a small area infested with S. occidentalis. Eight days after the transfer, 2 calves were apathetic and found dead within 24 h. Hence, the lot was relocated from the field. One of the animal was observed to be apathetic after 48 h and, it was in decubitus after 72 h, with opisthotone, forelimb pedaling, muscular tremors, hind limb incoordination, permanent decubitus, teeth grinding, apnea moments, and it died. Macroscopy revealed pale, multifocal to coalescent areas in the striated skeletal muscles of the pelvic limbs. The urinary bladder opening revealed dark-red colored urine. Histologically, a marked hyaline multifocal necrosis was observed in skeletal muscles. A large number of fragmented fibers, which is a characteristic of floccular necrosis, occasionally infiltrated by macrophages and a discrete amount of neutrophils, was visualized in addition to a discrete amount of satellite cells inside myocytes. Moderate multifocal vacuolization of hepatocytes was found in the liver, in the mediozonal region. The lung demonstrated moderate congestion and mild edema. Discussion: The diagnosis of Senna occidentalis intoxication was established by the association between epidemiological data, clinical signs, and macroscopic and histopathological lesions. The present case demonstrated spontaneous intoxication, probably facilitated by the recent transfer of the animals to the property, together with the time of the year that favors greater development of S. occidentalis, autumn. Plant intoxication affects 10% - 60% of the herd and has high lethality. The present study revealed that 7% of the animals were affected, probably influenced by the small area with plant availability. All animals that became ill died, confirming the high lethality of this intoxication. Disease progression in spontaneously affected calve manifests muscle weakness, pelvic limb incoordination, difficulty in moving, absence of rumen movements, and myoglobinuria. The clinical sign manifestation of muscle damage begins approximately in 1-2 weeks. The signs observed and the clinical course of the disease in the animal of the present case corroborate with that in the literature. The histopathological findings of this study revealed hyaline and flocculent necrosis of skeletal muscle fiber segments associated with the presence of satellite cells and macrophages. Although the frequency of spontaneous intoxication by Senna occidentalis is low, these cases must be reported for better knowledge and prevention of new instances. Additionally, breeders and handlers must know how to recognize this plant, because it must be eliminated from pastures to avoid significant losses. Keywords: muscle necrosis, myotoxic action, ruminants, toxic plant. Título: Surto de intoxicação por Senna occidentalis em bovinos Descritores: ação miotóxica, necrose muscular, planta tóxica, ruminantes.